Knowledge and compliances of safety measures among the solid waste collectors in Kathmandu valley - Shrestha, Shova (Journal of Patan Academy of Health Sciences, 2019)
Introductions: Safety measures of solid waste collectors are important to prevent occupational health problems. This study was designed to find out knowledge and compliance of safety measures among the solid waste collectors in Kathmandu Valley. Methods: A cross-sectional survey was conducted among solid waste collectors of Kathmandu metropolitan city from 12th August to 7th September 2018 by using a structured face to face interview schedule. Data were analysed by chi-square test, Pearson’s correlation and entered into SPSS 16 version. Results: Out of 117 waste collectors interviewed, more than 1/3rd (32.48%) had an adequate level of knowledge, and 1/5th (21.4%) had an adequate level of compliances. There was a weak negative correlation between level of knowledge and compliance on safety measures. Conclusions: One-third of respondents had an adequate level of knowledge about safety measures whereas only one fifth had an adequate level of compliances.